2017
DOI: 10.1051/0004-6361/201630269
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the wide-orbit circumbinary giant planet HD 106906

Abstract: Context. A giant planet has been recently resolved at a projected distance of 730 au from the tight pair of young (∼13 Myr) intermediate-mass stars HD 106906AB in the Lower Centaurus Crux (LCC) group. The stars are surrounded by a debris disk which displays a ring-like morphology and strong asymmetries at multiple scales. Aims. We aim to study the likelihood of a scenario where the planet formed closer to the stars in the disk, underwent inward diskinduced migration, and got scattered away by the binary star b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 72 publications
3
50
1
Order By: Relevance
“…Jílková & Portegies Zwart 2015). An ejection scenario with subsequent braking through a stellar fly-by appears unlikely in the light of the simulations by Rodet et al (2017). While not strictly excluded, in situ formation through disk instability appears unlikely (though not excluded) because large disks >700 AU have been rarely observed around forming stars.…”
Section: Summary and Discussionmentioning
confidence: 97%
“…Jílková & Portegies Zwart 2015). An ejection scenario with subsequent braking through a stellar fly-by appears unlikely in the light of the simulations by Rodet et al (2017). While not strictly excluded, in situ formation through disk instability appears unlikely (though not excluded) because large disks >700 AU have been rarely observed around forming stars.…”
Section: Summary and Discussionmentioning
confidence: 97%
“…In the latter scenario, the binary nature of HD 131399A could have played an active role. Rodet et al (2017) recently investigated a model to explain the formation of the distant planet (∼700 au) imaged around HD 106906. In this scenario, the recently discovered binary nature of HD 106906 (Lagrange et al 2016) plays a crucial role.…”
Section: Impact On the Planet Dynamical Historymentioning
confidence: 99%
“…A similar scenario could easily be considered for HD 131399Ab. Rodet et al (2017) has shown that a key point for this scenario is the eccentricity of the HD 106906 binary. The resonant eccentricity increase of the planet that furthermore leads to a close encounter is a direct consequence of the binary's eccentricity.…”
Section: Impact On the Planet Dynamical Historymentioning
confidence: 99%
See 2 more Smart Citations